Sea sand-coral-shell aggregate synergistically modified carbon sequestration concrete and preparation method and maintenance method thereof
Patent Information
- Application Number
- CN202611131929.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-29
AI Technical Summary
[0003]传统硅酸盐水泥混凝土存在高碳排放、高碱、不耐海水侵蚀的固有缺陷:目前工程结构混凝土仍以普通硅酸盐水泥为主要胶凝材料,其生产过程碳排放占全球人为排放量的8% 左右,单吨水泥碳排放高达 0.8~0.9t CO2
[0036]本发明以超硫酸盐水泥和海洋骨料为主要原料,结合特定的固碳剂、减水剂和氯盐抑制剂,在混凝土内部构件纳米填充、疏水成膜、低碱胶材三重耐久强化体系,混凝土在制备和养护过程中,固碳剂中的纳米二氧化硅自发填充于界面过渡区与毛细孔隙中,显著细化孔结构、降低渗透率;硅烷组分在孔壁与界面区原位水解缩合,形成连续、稳定、透气不透水的疏水膜层,大幅降低毛细吸水作用,阻断氯离子、水分、二氧化碳、硫酸盐的侵入通道;超硫酸盐水泥自身低碱、低钙、耐海水、耐氯盐的特性,可长期抑制碱骨料反应、钙溶蚀、钢筋锈蚀等病害发生,三者协同作用使混凝土氯离子扩散系数降低 60%-75%,抗碳化寿命提升3倍以上,抗海水侵蚀、抗冻融、抗干湿循环能力达到海洋工程结构材料的最高等级要求。具体地,本发明的固碳本质是以CO2为反应物、以钙离子为矿化中心、在加压与弱碱催化下实现的不可逆矿物碳酸化反应,并依托超硫酸盐水泥水化体系与珊瑚、贝壳多孔钙质骨料形成协同强化固碳机制,反应机制具体如下:
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of marine engineering building materials technology, and more specifically, to a carbon-fixing concrete synergistically modified with sea sand-coral-shell aggregate, its preparation method, and its curing method. Background Technology
[0002] In recent years, the demand for low-carbon, durable, and locally sourced concrete materials has increased dramatically in marine engineering, island and reef construction, and coastal infrastructure. However, in practical engineering and existing technologies, the three major areas of marine environmental concrete, carbon-fixing concrete, and marine aggregate resource utilization all suffer from common and insurmountable defects, as follows:
[0003] Traditional silicate cement concrete suffers from inherent drawbacks such as high carbon emissions, high alkali content, and poor resistance to seawater erosion. Currently, ordinary silicate cement remains the primary cementitious material in engineering structural concrete, accounting for approximately 8% of global anthropogenic carbon emissions during its production process, with each ton of cement emitting as much as 0.8-0.9 tons of CO2. Furthermore, silicate cement hydration products are highly alkaline and contain high levels of calcium hydroxide, making them highly susceptible to alkali-aggregate reactions, calcium dissolution, damage to the passivation film on reinforcing steel, and interfacial debonding and cracking under the corrosive environment of marine chloride, sulfate, and magnesium ions. More critically, silicate cement systems are unsuitable for deep carbonization and carbon fixation: excessive carbonization leads to CSH decalcification, strength reduction, and increased porosity, making it impossible to achieve simultaneous carbon fixation and reinforcement. Therefore, traditional high-carbon, high-alkali silicate cement systems have become a core bottleneck restricting the low-carbonization and long-life development of marine engineering.
[0004] The direct use of marine aggregates (sea sand, coral, shells) has fatal performance defects and cannot be used in structural concrete: Although marine aggregates such as sea sand, coral fragments, and shells can be sourced locally, existing technology shows that their direct use has four unacceptable defects: (1) Extremely high porosity and high water absorption. Coral and shells are biogenic calcium carbonate materials with well-developed internal interconnected pores and a water absorption rate of 18% to 25%, which is much higher than that of natural crushed stone, resulting in high water demand, uneven hydration, and many internal defects in concrete; (2) Low strength, high crushing value, and poor skeletal function. Shells and corals have poor edges and low strength after being crushed, and the crushing value can reach 30% to 40%, which significantly reduces the compressive, flexural, and impact resistance of concrete and makes it difficult to meet the requirements of load-bearing structures; (3) The interface transition zone (ITZ) is loose and weak. The porous aggregate surface adsorbs a large amount of water, resulting in an excessively high water-cement ratio in the interface zone, forming a loose, porous, and extremely low-strength transition zone, which becomes a preferred channel for the intrusion of chloride ions, carbon dioxide, and water; (4) Sea sand contains chloride, coral shells are prone to carbonization, and the structural durability is extremely poor. Sea sand introduces chloride ions, and coral shells themselves are carbonates, which will further deteriorate under the action of external CO2, resulting in rapid carbonization of concrete, large shrinkage, easy cracking, and a sharp increase in the risk of steel corrosion. Therefore, the existing technology can only use marine aggregates for non-structural, low-strength, and temporary projects, and cannot be applied on a large scale to the main structure.
[0005] Currently, modification technologies for corals, shells, and sea sand are mainly divided into three categories: physical strengthening, surface coating, and hydrophobic treatment. However, all of them have obvious limitations: physical modification can only remove impurities and cannot change the pore structure and water absorption characteristics, so the performance improvement is negligible; surface cement slurry coating and polymer impregnation are costly, complex, and difficult to scale up; the coating layer is easy to fall off and cannot improve the internal pores; although hydrophobic modification can reduce water absorption and improve carbonization resistance, it completely prevents CO2 from entering and cannot achieve carbon fixation. At the same time, it reduces the interfacial bonding strength, resulting in a decline in mechanical properties. Summary of the Invention
[0006] Based on the aforementioned technical problems in the existing technology, the present invention provides a carbon-fixing concrete synergistically modified with sea sand-coral-shell aggregate. Through a specific raw material ratio, a triple durability strengthening system of nanofiller, hydrophobic film formation, and low-alkali binder is constructed inside the concrete, enabling the concrete to have an ultra-long service life in the harsh marine environment.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows:
[0008] A type of carbon-fixing concrete synergistically modified with sea sand, coral, and shell aggregates, comprising, by weight, 360-450 parts of supersulfate cement, 1700-2200 parts of marine aggregates, 6-32 parts of carbon-fixing agent, 1.2-4.5 parts of water-reducing agent, 0.5-2.0 parts of chloride salt inhibitor, and 130-210 parts of seawater;
[0009] The marine aggregates include sea sand, coral fragments, and shell aggregates;
[0010] The carbon-fixing agent includes sodium bicarbonate, nano-silica, and silane hydrophobic modifier;
[0011] The seawater has a stable pH value of 8.0-8.3, a chloride ion content of ≤20g / L, and a sulfate ion content of ≤3.0g / L.
[0012] In some embodiments, the marine aggregate comprises, by weight percentage:
[0013] 35-55% sea sand
[0014] Coral fragments 25-40%
[0015] Shell aggregate 20-35%.
[0016] In some embodiments, the mass ratio of sodium bicarbonate, nano-silica, and silane hydrophobic modifier in the carbon-fixing agent is (5-10):1:(0.1-0.3).
[0017] In some embodiments, the mass ratio of the nano-silica to the organic amine in the chloride salt inhibitor is 1:(1-5).
[0018] In some embodiments, the supersulfate cement comprises, by weight percentage:
[0019] Granulated blast furnace slag 75-88%
[0020] 10-18% plaster
[0021] Silicate cement clinker 2-6%.
[0022] In some embodiments, the coral fragments have a particle size of 5-20 mm; the shell aggregate has a particle size of 4-16 mm; and the nano-silica has a particle size of 20-50 nm.
[0023] In some embodiments, the coral fragments and shell aggregates are pretreated by drying them and then calcining them at 500-600°C for 20-30 minutes.
[0024] In some embodiments, the raw materials of the water-reducing agent, by weight, include:
[0025] 60-90 parts of isopentenyl polyoxyethylene ether
[0026] 10-15 parts acrylic acid
[0027] 1-5 parts of dimethylaminoethyl methacrylate
[0028] Ammonium persulfate 0.5-2 parts
[0029] Sodium hypophosphite 0.1-0.9 parts.
[0030] In some embodiments, the chloride salt inhibitor comprises an organic amine; specifically, the organic amine comprises at least one of ethanolamines and isopropanolamines.
[0031] The present invention also provides a method for preparing concrete according to any of the above embodiments, the method comprising the following steps:
[0032] The coral fragments and shell aggregates are pretreated, then mixed with sea sand until homogeneous; next, supersulfate cement, carbon fixative, water-reducing agent, chloride inhibitor and seawater are added and mixed until homogeneous to obtain the concrete.
[0033] The present invention also provides a method for curing concrete according to any of the above embodiments, the method comprising the following steps:
[0034] After pretreatment of the coral fragments and shell aggregates, they are mixed with sea sand until homogeneous. Then, supersulfate cement, carbon fixative, water-reducing agent, chloride inhibitor, and seawater are added and mixed until homogeneous to obtain the concrete. The concrete is poured into shape and cured under standard conditions for at least 7 days. Then, it is placed in an environment of 23-28℃, filled with CO2, and with a pressure of 3.0-7.5MPa for at least 4 hours of curing.
[0035] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0036] This invention uses supersulfate cement and marine aggregates as main raw materials, combined with specific carbon-fixing agents, water-reducing agents, and chloride inhibitors. It establishes a triple durability strengthening system for concrete internal components, involving nano-filling, hydrophobic film formation, and low-alkali adhesives. During concrete preparation and curing, nano-silica in the carbon-fixing agent spontaneously fills the interface transition zone and capillary pores, significantly refining the pore structure and reducing permeability. Silane components undergo in-situ hydrolysis and condensation at the pore walls and interface, forming a continuous, stable, air-permeable but water-impermeable hydrophobic film, greatly reducing capillary water absorption and blocking the intrusion channels of chloride ions, moisture, carbon dioxide, and sulfates. The supersulfate cement's inherent low alkali, low calcium, seawater resistance, and chloride resistance can long-term inhibit alkali-aggregate reaction, calcium dissolution, and steel corrosion. The synergistic effect of these three components reduces the chloride ion diffusion coefficient of concrete by 60%-75%, increases carbonation resistance by more than three times, and achieves the highest level of resistance to seawater erosion, freeze-thaw cycles, and wet-dry cycles required for marine engineering structural materials. Specifically, the carbon fixation mechanism of this invention is an irreversible mineral carbonation reaction achieved under pressure and weak alkali catalysis, using CO2 as the reactant and calcium ions as the mineralization center. It also relies on a supersulfate cement hydration system to form a synergistic carbon fixation mechanism with porous calcareous aggregates from corals and shells. The reaction mechanism is as follows:
[0037] The calcium silicate hydrate (CSH), ettringite, and a small amount of calcium hydroxide produced during the hydration of supersulfate cement continuously dissociate into Ca. 2+ With CO3 in the solution 2- On the one hand, aragonite and calcite in corals and shells undergo surface dissolution under the action of water film and pressure, releasing calcium carbonate. 2+It participates in recarbonation crystallization; the nano-SiO2 in the carbon-fixing agent acts as a heterogeneous nucleus, inducing calcium carbonate to precipitate uniformly as nano-sized calcite and aragonite, avoiding internal stress caused by coarse crystals, allowing the carbonation products to fill pores in situ and densify the matrix, achieving simultaneous mineral stabilization and structural enhancement; sodium bicarbonate maintains a weakly alkaline environment in the pore solution through pH buffering, significantly increasing the rate of CO2 hydrolysis and carbonate generation, reducing the activation energy of the carbonation reaction, and promoting the reaction to spontaneously proceed towards CaCO3 precipitation; the silane hydrophobic modifier forms a hydrophobic siloxane film on the pore wall, inhibiting water and ion migration, further improving the chemical stability of the carbon-fixed products. Under pressure, the reaction equilibrium further shifts towards mineralization, and the carbonation rate and conversion efficiency are greatly improved. Unlike ordinary silicate cement systems, the low alkali, low calcium, and high alumina characteristics of supersulfate cement avoid the CO2 absorption hindrance caused by high pH, allowing the carbonation reaction to continue deep within the matrix, achieving uniform carbonation throughout the entire area, rather than being limited to the surface of the specimen. The nano-calcium carbonate generated by carbon fixation fills the interfacial transition zone and capillaries, significantly refining the pore size and reducing the interconnected porosity, forming a physical barrier layer that prevents the fixed carbon from being desorbed and released. The hydration and carbonation products of the supersulfate cement itself are highly compatible, exhibiting minimal volume deformation and no significant expansion or cracking, ensuring the long-term stability of the carbon sequestration structure.
[0038] Furthermore, this invention also provides a method for curing concrete after molding. This method involves curing the molded concrete component under standard conditions, followed by a carbonation reaction under pressure. Under pressure carbonation, CO2 molecules migrate from the gas phase to the liquid phase within the concrete pores, and their dissolution behavior follows Henry's Law. Increased pressure significantly improves the solubility and diffusion coefficient of CO2 in the pore solution. This invention, through carbonation in a pressure carbonation environment, enables CO2 to rapidly penetrate the concrete surface and enter the interfacial transition zone and the internal pores of the aggregate. Simultaneously, the weakly alkaline environment provided by sodium bicarbonate reduces the gas-liquid interfacial resistance, promoting the hydrolysis of CO2 to generate H2CO3 and its rapid dissociation into HCO3. - With CO3 2- This provides highly reactive precursors for subsequent mineralization reactions, accelerating the carbon fixation process from a kinetic perspective. Ultimately, CO2 is permanently solidified in the concrete matrix in the form of stable carbonate minerals, achieving true mineral carbon fixation and long-term storage.
[0039] By using the method of this invention to cure concrete, the carbon sequestration capacity of concrete can be effectively improved, as well as its compressive strength and resistance to chloride ion diffusion, thereby enhancing its service life in harsh marine environments. Detailed Implementation
[0040] Numerous specific details are set forth in the following description to provide a full understanding of the invention. However, the invention can be practiced in many other ways different from those described herein, and similar modifications can be made by those skilled in the art without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0042] The following are some of the raw materials used in the embodiments and comparative examples of this invention, as well as the process procedures for specimen preparation and testing:
[0043] (1) Raw materials
[0044] Supersulfate cement: Composed of 82% granulated blast furnace slag, 15% natural anhydrous gypsum, and 3% silicate cement clinker, with a specific surface area of 400 m². 2 / kg;
[0045] Sea sand: fineness modulus 2.7, chloride ion content 0.05%, particle size 0-5mm, apparent density 2650kg / m³ 3 The gradation is continuous and the texture is uniform.
[0046] Coral fragments: 5mm-20mm in diameter, 96% calcium carbonate content, obtained from coral after crushing, washing, drying and grading;
[0047] Shell aggregate: Particle size 4mm-16mm, shell thickness ≥2mm, calcium carbonate content 98%, obtained from shells through crushing, washing, drying and grading;
[0048] Carbon fixing agent: sodium bicarbonate, nano silica (particle size 5-20nm), and silane coupling agent KH-550 are composed in a mass ratio of 6:1:0.2;
[0049] Mixing water: On-site natural seawater, pH=8.1, chloride ion content 18.2g / L, sulfate ion content 2.7g / L, used directly without treatment;
[0050] Water-reducing agent: By weight, it consists of 75 parts isopentenyl polyoxyethylene ether, 12.5 parts acrylic acid, 2.5 parts dimethylaminoethyl methacrylate, 1.2 parts ammonium persulfate and 0.5 parts sodium hypophosphite. Before use, mix the raw materials, add water to make 100 parts, react, and let stand for 2 hours.
[0051] Chloride inhibitor: Triethanolamine;
[0052] CO2 gas: purity 99.9%, meeting the requirements of GB / T 6052-2011 standard;
[0053] Test mold: 70.7mm×70.7mm×70.7mm high-precision steel test mold, with a dimensional error of ±0.1mm.
[0054] (2) Unify the basic process flow
[0055] All embodiments and comparative examples strictly followed the same process flow:
[0056] Coral and shell aggregate pretreatment: washing, grading, drying at 50℃, calcining at 550℃ for 30 min and then cooling;
[0057] Concrete mixing regime: dry mixing 120s, wet mixing 180s, low speed 60r / min, high speed 90r / min;
[0058] Molding process: two-layer casting, standard vibrating table compaction, surface smoothing and polishing, film covering and static curing for 24 hours;
[0059] Curing schedule: Demolding after 24 hours, standard curing for 28 days (temperature 20±2℃, humidity ≥95%).
[0060] Pressure carbonization process: vacuum -0.09MPa, set target pressure, heat and pressure hold at 25℃ for 6 hours, then slowly depressurize;
[0061] Performance tests: compressive strength GB / T 50081-2019, carbonization depth GB / T 50082-2019, carbon fixation amount TG-DSC thermogravimetric method, porosity mercury intrusion porosimetry MIP, chloride ion diffusion coefficient RCM method.
[0062] Example 1
[0063] A carbon-fixing concrete synergistically modified with sea sand, coral, and shell aggregates, comprising the following raw materials by weight:
[0064] Supersulfate cement: 380 parts; Composite marine aggregate: 1850 parts (by mass percentage, sea sand 45%, coral 30%, shell 25%); Natural seawater: 210 parts; Carbon fixation agent: 28 parts (by mass ratio, NaHCO3: nano SiO2: KH-550 = 6:1:0.2); Seawater resistant polycarboxylate superplasticizer: 4.2 parts; Chloride inhibitor: 1.8 parts.
[0065] (2) Implementation steps
[0066] Following a standardized process, 555 parts of coral fragments and 462.5 parts of shell aggregate were first weighed and placed in a crucible for calcination at 550℃ for 30 minutes, followed by furnace cooling. The calcined coral fragments and shell aggregate were then mixed with 832.5 parts of sea sand and fed into a twin-shaft forced mixer. 380 parts of supersulfate cement were then added, and the mixture was dry-mixed at a low speed of 60 r / min for 90 seconds, followed by high-speed dry-mixing at 90 r / min for 60 seconds to obtain the dry-mixed material. Natural seawater, carbon fixative, water-reducing agent, and triethanolamine were pre-mixed and stirred for 3 minutes to form a homogeneous solution. This solution was then added to the mixer and wet-mixed at a low speed for 60 seconds, followed by high-speed wet-mixing for 120 seconds to ensure the mixture was homogeneous, free of lumps, and did not segregate, with a slump controlled at 160±20 mm.
[0067] The mixture was placed into a 70.7 mm mold in two layers. The first layer was vibrated for 60 s and the second layer for 90 s. After the surface was smoothed, the mold was covered and left to stand for 24 h. Then, the mold was removed and the molded specimen was placed in a standard curing room for 28 days. After curing, the specimen was placed in a high-pressure carbonization reactor, the reactor door was closed, and a vacuum was drawn to -0.09 MPa. The pressure was maintained for 10 min to remove the internal air. Then, CO2 was slowly introduced at a rate of 0.2 MPa / min until the pressure reached 5 MPa. The mixture was kept at 25 °C and pressure for 6 h. After the reaction was completed, the pressure was slowly released at a rate not exceeding 0.1 MPa / min. The specimen was then removed and left to stand at room temperature for 24 h before various performance tests were performed.
[0068] Example 2
[0069] (1) Raw material ratio
[0070] The raw material ratio in this embodiment is exactly the same as that in Example 1.
[0071] (2) Implementation steps
[0072] The implementation steps of this embodiment are the same as those of Embodiment 1, except that the pressure during the pressurization carbonization stage is 3.0 MPa.
[0073] Example 3
[0074] (1) Raw material ratio
[0075] The raw material ratio in this embodiment is exactly the same as that in Example 1.
[0076] (2) Implementation steps
[0077] The implementation steps of this embodiment are the same as those of Embodiment 1, except that the pressure during the pressurized carbonization stage is 7.5 MPa.
[0078] Example 4
[0079] (1) Raw material ratio
[0080] The raw materials in this embodiment, by mass parts, consist of the following:
[0081] Supersulfate cement: 380 parts; Composite marine aggregate: 1850 parts (60% sea sand, 25% coral, 15% shell); Natural seawater: 210 parts; Composite modified carbon fixative: 28 parts; Water-reducing agent: 4.2 parts; Chloride inhibitor: 1.8 parts.
[0082] (2) Implementation steps
[0083] The implementation steps of this embodiment are the same as those of Embodiment 3.
[0084] Example 5
[0085] (1) Raw material ratio:
[0086] Supersulfate cement: 380 parts; composite marine aggregate: 1850 parts (40% sea sand, 35% coral, 25% shell); the remaining components are the same as in Example 3.
[0087] (2) Implementation steps
[0088] The implementation steps of this embodiment are the same as those of Embodiment 3.
[0089] Example 6
[0090] (1) Raw material ratio:
[0091] Supersulfate cement: 380 parts; composite marine aggregate: 1850 parts (30% sea sand, 30% coral, 40% shell); the remaining components are the same as in Example 3.
[0092] (2) Implementation steps
[0093] The implementation steps of this embodiment are the same as those of Embodiment 3.
[0094] Example 7
[0095] (1) Raw material ratio:
[0096] Supersulfate cement: 380 parts; composite marine aggregate: 1850 parts; the carbon fixation agent ratio was changed to NaHCO3: nano SiO2: silane hydrophobic agent = 5:1:0.1; the rest was the same as in Example 3.
[0097] (2) Implementation steps
[0098] The implementation steps of this embodiment are the same as those of Embodiment 3.
[0099] Example 8
[0100] (1) Raw material ratio:
[0101] Supersulfate cement: 380 parts; composite marine aggregate: 1850 parts; the carbon fixation agent ratio was changed to NaHCO3: nano SiO2: silane hydrophobic agent = 7:1:0.3; the rest was the same as in Example 3.
[0102] (2) Implementation steps
[0103] The implementation steps of this embodiment are the same as those of Embodiment 3.
[0104] Comparative Example 1
[0105] (1) Raw material ratio
[0106] It is exactly the same as Example 3.
[0107] (2) Implementation steps
[0108] The coral and shell aggregates were not calcined and were directly mixed with sea sand. The other mixing system, molding method, curing process, pressure, temperature and time of carbonization were completely consistent with those in Example 3.
[0109] Comparative Example 2
[0110] (1) Raw material ratio:
[0111] Same as Example 3, except that no carbonizing agent is added.
[0112] (2) Implementation steps
[0113] The implementation steps are the same as those in Example 3.
[0114] Comparative Example 3
[0115] (1) Raw material ratio
[0116] 380 parts of PO 42.5 ordinary Portland cement were used to completely replace the supersulfate cement, and the remaining raw materials and dosages were the same as in Example 3.
[0117] (2) Implementation steps
[0118] The implementation steps are the same as those in Example 3.
[0119] Comparative Example 4
[0120] (1) Raw material ratio
[0121] The raw material ratios in this comparative example are the same as those in Example 3.
[0122] (2) Implementation steps
[0123] The implementation steps and other conditions are exactly the same as in Example 3, except that the high-pressure carbonization kettle is not used for pressurized CO2 carbonization, and the performance test is carried out directly.
[0124] Comparative Example 5
[0125] (1) Raw material ratio
[0126] The raw material ratios in this comparative example are exactly the same as those in Example 3.
[0127] (2) Implementation steps
[0128] The implementation steps of this comparative example are the same as those of Example 3, except that the pressure during the pressurized carbonization stage is 1.0 MPa.
[0129] Comparative Example 6
[0130] (1) Raw material ratio:
[0131] All aggregates were natural crushed stone and river sand, totaling 1850 parts by weight. No sea sand, coral, or shells were used. The rest was the same as in Example 3.
[0132] (2) Implementation steps
[0133] The implementation steps are exactly the same as those in Example 3.
[0134] The relevant performance test results of the examples and comparative examples are shown in Table 1 and Table 2, respectively.
[0135] Comparative Example 7
[0136] (1) Raw material ratio:
[0137] Similar to Example 3, except that the water-reducing agent used is a commercially available water-reducing agent, the main components of which are: 75 parts of isopentenyl polyoxyethylene ether, 12.5 parts of acrylic acid, 1.2 parts of ammonium persulfate, and 0.5 parts of sodium hypophosphite; before use, the raw materials are mixed, water is added to make up to 100 parts, and after reaction, it is allowed to stand for 2 hours.
[0138] (2) Implementation steps
[0139] The implementation steps are the same as those in Example 3.
[0140] Table 1. Performance test results of specimens in Examples 1-8
[0141]
[0142] Table 2 Performance test results of specimens from Comparative Examples 1-6
[0143]
[0144] As shown in Tables 1 and 2, this invention, through the synergistic effects of a supersulfate cement system, marine aggregate composite, semi-wet modification, pressurized carbon fixation, and hydrophobic chloride inhibition, significantly improves concrete's compressive strength, carbon fixation content, pore structure, and resistance to chloride ion penetration.
[0145] (1) Effect of CO2 carbonation pressure on concrete properties
[0146] As can be seen from Examples 1-3, as the CO2 carbonation pressure gradually increases from 3.0 MPa to 7.5 MPa, the carbonation depth, compressive strength, and carbon fixation amount of concrete all show a significant upward trend, while the chloride ion diffusion coefficient continues to decrease. This indicates that increasing the CO2 pressure can significantly improve the solubility and diffusion rate of CO2 in the pore solution, promote the carbonation reaction to penetrate deeper into the concrete, generate more calcium carbonate products and fill the pores, thereby achieving matrix densification, strength improvement and a significant increase in carbon fixation efficiency. The experimental results are consistent with the supercritical carbonation strengthening mechanism.
[0147] (2) The effect of marine aggregate proportion on concrete performance
[0148] As shown in Examples 3-6, under the same carbonation pressure and preparation process, the aggregate ratio of sea sand to coral to shell has a significant impact on the workability, mechanical properties, carbon fixation capacity, and durability of concrete. When the aggregate ratio is sea sand:coral:shell = 45:30:25, the concrete exhibits the best overall performance, with a compressive strength of 42.6 MPa and a carbon fixation capacity of 102.6 kg CO2 / m³. 3 The chloride ion diffusion coefficient is as low as 2.9 × 10⁻⁶. -12 m 2 An excessively high proportion of sea sand will reduce the system's carbon sequestration capacity; increasing the proportion of coral helps improve carbon sequestration, but excessive amounts will lead to increased water absorption and decreased strength; an excessively high proportion of shells will increase internal porosity, resulting in decreased mechanical properties and durability. Therefore, a ratio of 45% sea sand, 30% coral, and 25% shells achieves the optimal balance between skeletal support, porosity control, and calcium source supply.
[0149] (3) The effect of carbonation agents on concrete performance
[0150] As can be seen from Examples 3, 7, and 8, the ratio of sodium bicarbonate, nano-silica, and silane coupling agent in the composite modified carbonitriding agent has a significant impact on carbonation efficiency, strength development, and durability. When the ratio is sodium bicarbonate: nano-silica: silane hydrophobic modifier = 6:1:0.2, the concrete exhibits the highest degree of carbonation, the greatest strength improvement, and the lowest chloride ion penetration.
[0151] (4) Comparison of the present invention with untreated aggregate
[0152] Comparing Example 3 with Comparative Example 1, it can be seen that when using untreated coral shell aggregate, the concrete compressive strength is only 23.8 MPa and the carbon sequestration is only 21.5 kg CO2 / m³. 3 The chloride ion diffusion coefficient is as high as 12.7 × 10⁻⁶. -12 m 2 / s, the porosity decreases by only 8.3%. However, after calcination, the compressive strength increases by 79%, the carbon fixation content increases by 377%, the chloride ion diffusion coefficient decreases by 77%, and the porosity decreases by 37.2%.
[0153] (5) Comparison of the present invention with pure water atomization carbonization
[0154] Comparing Example 3 with Comparative Example 2, it can be seen that without the addition of a carbonizing agent, the carbon sequestration content of the concrete is 63.7 kg CO2 / m³. 3 The compressive strength is 35.2 MPa, and the chloride ion diffusion coefficient is 6.8 × 10⁻⁶. -12 m 2 / s. Under the same process conditions, the introduction of a carbonizing agent in this invention increases the carbon fixation amount by 61%, compressive strength by 21%, and decreases the chloride ion diffusion coefficient by 57%. This demonstrates that the carbonizing agent can significantly improve carbonization efficiency and interfacial properties.
[0155] (6) Comparison of the present invention with silicate cement system
[0156] Comparing Example 5 with Comparative Example 3, it can be seen that after replacing supersulfate cement with silicate cement, the carbon sequestration of the concrete is 77.3 kg CO2 / m³. 3 The compressive strength is 37.5 MPa, and the chloride ion diffusion coefficient is 5.6 × 10⁻⁶. -12 m 2 / s. This invention, by employing a supersulfate cement system, increases carbon sequestration by 32.7%, compressive strength by 13.6%, reduces the chloride ion diffusion coefficient by 48%, and lowers carbon emissions from the cementing system by over 70%. This indicates that supersulfate cement is more suitable for marine environments and deep carbonization systems, achieving a synergistic improvement in low carbon, high carbon sequestration, and high durability.
[0157] (7) Comparison of the present invention with non-pressurized carbonization
[0158] Comparing Example 3 with Comparative Example 4, it can be seen that without pressurized carbonation, the carbon sequestration content of the concrete is only 46.8 kg CO2 / m³. 3 The compressive strength is 32.5 MPa, and the chloride ion diffusion coefficient is 8.5 × 10⁻⁶. -12 m 2 / s. This invention achieves a 119% increase in carbon content, a 31% increase in compressive strength, and a 66% decrease in chloride ion diffusion coefficient through pressurized carbonization under specific pressure. This demonstrates that pressurized carbonization can achieve uniform carbonization, internal densification, and comprehensive performance improvement.
[0159] (8) Comparison of the present invention with natural sand and gravel concrete
[0160] Comparing Example 3 with Comparative Example 5, it can be seen that the concrete using natural crushed stone and river sand has slightly higher strength, but its carbon sequestration is only 41.6 kg CO2 / m³. 3 This invention, while using 100% marine aggregate and achieving a 147% increase in carbon sequestration, still maintains a compressive strength of 42.6 MPa, meeting the requirements for structural concrete. This achieves a balance between ecological benefits, carbon sequestration benefits, and structural performance.
[0161] (9) Performance comparison between the self-made functional water-reducing agent of this invention and commercially available ordinary polycarboxylate water-reducing agent
[0162] When using commercially available general-purpose polycarboxylate superplasticizers, the 28-day compressive strength of concrete is only 34.1 MPa. The modified polycarboxylate superplasticizer of this invention, containing dimethylaminoethyl methacrylate, can increase the compressive strength to 42.6 MPa, a strength increase of 24.9%, a carbon fixation capacity increase of 41.9%, and a chloride ion penetration resistance increase of 53.2%. In the superplasticizer composition of this invention, the long side chain of isopentenyl polyoxyethylene ether ensures high water reduction and slump retention, acrylic acid provides basic dispersion and anchoring, and dimethylaminoethyl methacrylate achieves a three-in-one effect of chloride inhibition, interface strengthening, and stable carbonization environment. It is highly compatible with supersulfate cement, seawater, and sea sand-coral-shell composite aggregates, making it an indispensable key component for achieving "high carbon fixation, high strength, and high durability" marine concrete.
[0163] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0164] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the appended claims.
Claims
1. A carbon-fixing concrete synergistically modified with sea sand-coral-shell aggregate, characterized in that, By weight, its raw materials include: 360-450 parts of supersulfate cement, 1700-2200 parts of marine aggregate, 6-32 parts of carbon fixative, 1.2-4.5 parts of water-reducing agent, 0.5-2.0 parts of chloride salt inhibitor and 130-210 parts of seawater; The marine aggregates include sea sand, coral fragments, and shell aggregates; The carbon-fixing agent includes sodium bicarbonate, nano-silica, and silane hydrophobic modifier; The seawater has a stable pH value of 8.0-8.3, a chloride ion content of ≤20g / L, and a sulfate ion content of ≤3.0g / L; The marine aggregate, by mass percentage, comprises: 35-55% sea sand Coral fragments 25-40% Shell aggregate 20-35%; In the carbon-fixing agent, the mass ratio of sodium bicarbonate, nano-silica, and silane hydrophobic modifier is (5-10):1:(0.1-0.3). The supersulfate cement comprises, by weight percentage: Granulated blast furnace slag 75-88% 10-18% plaster 2-6% silicate cement clinker; The coral fragments and shell aggregates are first pretreated by drying them and then calcining them at 500-600℃ for 20-30 minutes.
2. The carbon-fixing concrete synergistically modified with sea sand-coral-shell aggregate according to claim 1, characterized in that, The chloride salt inhibitors include organic amines.
3. The carbon-fixing concrete synergistically modified with sea sand-coral-shell aggregate according to claim 1, characterized in that, The coral fragments have a particle size of 5-20 mm; the shell aggregate has a particle size of 4-16 mm; and the nano-silica has a particle size of 20-50 nm.
4. The carbon-fixing concrete synergistically modified with sea sand-coral-shell aggregate according to claim 1, characterized in that, The raw materials of the water-reducing agent, by weight, include: 60-90 parts of isopentenyl polyoxyethylene ether 10-15 parts acrylic acid 1-5 parts of dimethylaminoethyl methacrylate Ammonium persulfate 0.5-2 parts Sodium hypophosphite 0.1-0.9 parts.
5. The method for preparing carbon-fixing concrete synergistically modified with sea sand-coral-shell aggregate according to any one of claims 1-4, characterized in that, Includes the following steps: The coral fragments and shell aggregates are pretreated, then mixed with sea sand until homogeneous; next, supersulfate cement, carbon fixative, water-reducing agent, chloride inhibitor and seawater are added and mixed until homogeneous to obtain the concrete.
6. The curing method for the synergistic modification of carbon-fixing concrete using sea sand-coral-shell aggregate as described in any one of claims 1-4, characterized in that, Includes the following steps: After pretreatment of the coral fragments and shell aggregates, they are mixed with sea sand until homogeneous. Then, supersulfate cement, carbon fixative, water-reducing agent, chloride inhibitor, and seawater are added and mixed until homogeneous to obtain the concrete. The concrete is poured into shape and cured under standard conditions for at least 3 days. Then, it is placed in an environment of 23-28℃, filled with CO2, and with a pressure of 3.0-7.5MPa for at least 4 hours of heat and pressure curing.
Citation Information
Patent Citations
Low-carbon and carbon-absorbing concrete and preparation method thereof
CN103193434A
Low-carbon island reef full-coral seawater concrete and preparation method thereof
CN118084439A
Supersulfate concrete capable of solidifying chloride ions in sea sand in situ and preparation method thereof
CN122167120A
Carbonization curing preparation method of chloride ion resistant sea sand concrete
CN122380891A